Selecting Indicators to Assess the Sustainability of Urban Freight Transport Using a Multi-Criteria Analysis - Hana Ayadi; Mounir Benaissa; Nadia Hamani; Lyes Kermad (Logistics, 2024)
Background: Urban freight transport has recently garnered significant attention from both professionals and academics due to its pivotal role in fostering economic and social development. Despite notable progress, this sector faces challenges that hinder its long-term sustainability. Addressing these issues and ensuring the lasting sustainability of urban freight transport require a thorough assessment and monitoring process utilizing specific indicators. Methods: This paper introduces a set of indicators developed using a three-step methodology aimed at assessing the sustainability progress of urban freight transport. Initially, we present a long list of indicators drawn from the existing literature. Subsequently, we consider five essential properties: achievability, data availability, predictability, relevance, and comprehensibility. Lastly, we apply a multi-criteria analysis methodology that utilizes these properties to assess the long lists encountered during the selection process. The chosen indicators are those that do not register a value of “0” for any of the specified properties. To enhance reliability, the indicators are collaboratively identified by a minimum of two experts. Results: By carefully selecting 18 indicators based on five sustainability dimensions (economic, environmental, social/societal, political, and spatial), our approach ensures a robust evaluation framework. Conclusions: These indicators serve as valuable tools for stakeholders in comprehensively evaluating the sustainability aspects of urban freight transport.